Rhinocerebral mucormycosis: A report of two cases - Venkateswarlu Nallapu; Hima Bindu Vuppalapati; Sailaja Sambhana; Bhavya Balasankulu (Wolters Kluwer Medknow Publications, 2015)
Mucormycosis is an acute opportunistic infection caused by saprophytic fungus of class Phycomycetes order Mucorales and family Mucoracae, found in soil, bread molds, and decaying fruits and vegetables. Even though this fungus is ubiquitous in the nature, the disease is usually prevented by immune system and is therefore rare. Rhizopus, Rhizomucor, Absidia and Cunninghamella are the most common species associated with Mucormycosis. Diabetes, chronic kidney disease, desferroxamine use in dialysis, leukemia, lymphoma, immunocompromised state, burns and open wounds are the risk factors of mucormycosis. Out of six clinical entities of mucormycosis, rhinocerebral mucormycosis is the most common variety which includes three subtypes rhinomaxillary, rhino-orbital and rhino-orbitocerebral mucormycosis. Here are two case reports of Rhinocerebral mucormycosis of different subtypes emphasizing the role of early detection of the disease to limit the spread of infection and reducing the morbidity and mortality.